Prescription Patterns, Recurrence, and Toxicity Rates of Adjuvant Treatment for Stage III/IV Melanoma—A Real World Single-Center Analysis - Michèle Hoffmann; Stefanie Hayoz; Berna C. Özdemir (Biology, 2022)
Approved adjuvant treatment options for stage III melanoma are the immune checkpoint inhibitors (ICI) pembrolizumab and nivolumab, and in presence of a BRAF V600E/K mutation additionally dabrafenib in combination with trametinib (BRAFi/MEKi). This study aims to describe prescription patterns and recurrence and toxicity rates of adjuvant-treated melanoma patients from the Cancer Center of the University Hospital Bern, Switzerland. One hundred and nine patients with an indication for adjuvant treatment were identified. Five (4.6%) had contraindications and, as such, were not proposed any adjuvant treatment, while 10 patients (9.2%) declined treatment. BRAF status was known for 91 (83.5%) patients. Of 40 (36.7%) patients with BRAF V600E/K melanoma, pembrolizumab was prescribed to 18 (45.0%), nivolumab to 16 (40.0%), and dabrafenib/trametinib to three (7.5%) patients. Grade 3–4 toxicity was reported in 18.9% and 16.7% of all the patients treated with pembrolizumab and nivolumab, respectively. No toxicities were observed for dabrafenib/trametinib. Thirty-eight percent of the patients treated with pembrolizumab and 40.0% of those treated with nivolumab relapsed. No relapses were reported for dabrafenib/trametinib. Prescription patterns indicate a clear preference for adjuvant ICI treatment.